A checklist of Pontarachnidae (Acari: Hydrachnidia) and notes on distributional patterns of the species - Chatterjee, Tapas; Schizas, Nikolaos V.; Pešić, Vladimir (Zootaxa, 2019)
A worldwide checklist of the pontarachnid mites is provided based on published reports and original data. A total of 53 valid species of pontarachnid mites have been compiled, of which the genus Pontarachna includes 30 species, while 23 species belong to the genus Litarachna. The highest number of species (n=16) is reported from the marine province Tropical West of the Pacific Ocean. A deutonymph of Litarachna triangularis is reported here from Dongsha Atoll, Taiwan. Patterns of endemism and seemingly incomplete species distributional records are the result of a lack of intensive faunistic surveys in different parts of the world. The taxonomy of Pontarachnid mites will be improved by the use of mite-specific sampling methods and the application of molecular phylogenetics.